Occurrence of two autochthonous cases of American cutaneous leishmaniasis in the neighborhood of Caju, city of Rio de Janeiro, Brazil - Fred Bernardes Filho; Danielle Cristine Bonatto; Gustavo Martins; Leonardo de Medeiros Maier; José Augusto da Costa Nery; Luna Azulay-Abulafia (Sociedade Brasileira de Dermatologia, 2014)
American cutaneous leishmaniasis is in full geographic expansion in Brazil and it is considered among the infectious and parasitic diseases of utmost importance worldwide, not only by its frequency, but mainly by therapeutic difficulties, deformities and sequelae that may result. In the state of Rio de Janeiro, the first autochthonous case of American cutaneous leishmaniasis was registered by Rabello in 1913. The authors report two cases of the disease in the region around the Cemetery São Francisco Xavier, in the Caju neighborhood, Rio de Janeiro city, and emphasize the need for actions that aim to early diagnosis and treatment of American cutaneous leishmaniasis cases.